Retraction: [Determination of Neophobia Levels of Students Studying in Gastronomy Departments of Higher Education Institutions in Northern Cyprus] - Özçil, İhsan Erol (Food Science and Engineering, 2024)
Retraction Note: Volume 6 Issue 2, FSE-8171 DOI: https://doi.org/10.37256/fse.6220258171 The food and beverage industry ranks among the sectors that are constantly open to innovation. Food neophobia refers to individuals’ reluctance to consume foods they are not accustomed to or have not tried before. In the process of forming and maintaining eating habits, individuals may tend to prefer certain foods and not be open to new foods. We conducted our research on the students of the Culinary Arts Department at the American University of Cyprus and the Girne American University to look into this subject more in-depth. This study was conducted using the Food Neophobia Scale (FNS) to understand students’ fear of novelty in their food preferences. The data obtained from 182 students through face-to-face interviews and a supplemented questionnaire were evaluated and analyzed using statistical methods. The results of the study revealed that students generally showed an aversion to new foods. This reluctance has often caused individuals to avoid trying foods that are different from what they are used to. It is therefore seen as a critical step in understanding future trends in the food sector. The results of such research can be used to understand the younger generation’s approach to new foods, the industry’s product development strategies, consumer demands, educational institutions to update their curricula, and students to introduce innovative food products. Since there is no study on food neophobia between university students in Northern Cyprus, this research will shed light on future studies.